Examining the effect of educational games on middle school students’ attitudes towards physical education and sports lessons and their motor skills - Kezban Gülşen Eşkil; Belgin Gökyürek (BMC Sports Science, Medicine and Rehabilitation)
Abstract Aim The aim of this research is to examine the changes in children’s motor skills and attitudes towards the lesson through the use of 12-week educational games as an addition to the existing physical education and sports curriculum and the elective sports and physical activity course. Methods The study was conducted with 5th and 6th-grade students from Şehit Yakup Çınar Middle School in Sincan district, Ankara during the 2022-2023 Academic Year. The sample group was determined using the simple random sampling method. The experimental group consisted of 136 students, while the control group comprised 127 students. During the 12-week period, the experimental group received a total of 4 class hours per week of additional physical education and sports lessons and elective sports and physical activity classes within their regular school schedule, where educational games were incorporated. On the other hand, the control group did not receive any additional program beyond the regular curriculum. Data collection instruments included a Personal Information Form containing information regarding participants’ gender and grade, the Motor Skill Measurement Tests, and the Physical Education and Sports Scale for Secondary School Students to measure their attitudes towards physical education and sports lessons. Pre-test and post-test measurements were conducted for both the control and experimental groups to assess the impact of the educational games. Statistical analysis was performed using SPSS 25.0 software. Skewness and kurtosis values (-1.5 and +1.5) were examined for normality distribution. The paired samples t-test was used to determine the differences within the control and experimental groups in the pre-test and post-test data. Additionally, the independent samples t-test was used for intergroup comparisons between the experimental and control groups. Results The findings revealed that the 12-week educational games applied to the 5th and 6th-grade students had a significant positive impact on the experimental group regarding flamingo balance, flexibility, 30-second sit-ups, and attitudes. However, there was no significant difference between the groups in the standing long jump and 20-meter sprint parameters. Conclusions As a result, the findings revealed that the 12-week educational games applied to the 5th and 6th-grade students had a significant positive impact on the experimental group regarding flamingo balance, flexibility, 30-second sit-ups, and attitudes. However, there was no significant difference between the groups in the standing long jump and 20-meter sprint parameters.